2017
DOI: 10.1007/s10068-017-0075-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and toxin type of Clostridium perfringens in beef from four different types of meat markets in Seoul, Korea

Abstract: Beef is the primary source of foodborne poisoning caused by . We investigated the prevalence of in retail beef from four different types of meat markets in Seoul using a standard culture method and real-time PCR assay. From June to September 2015, 82 beef samples were collected from 6 department stores (=12), 14 butcher shops (=28), 16 traditional markets (=32), and 5 supermarkets (=10). The culture method and real-time PCR assay revealed that 4 (4.88%) and 10 (12.20%) samples were positive for C. perfringens,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…It produces Clostridium perfringens alpha toxin (CPA) along with enterotoxin (CPE) with or without Clostridium perfringens beta 2 toxin (CPB2) [ 31 , 32 ]. It has been reported that C. perfringens is readily detected in foods such as pork, beef, chicken, and sheep [ 33 - 35 ]. In this study, the relative abundance of C. perfringens in chicken feces was the highest among three different livestock species.…”
Section: Discussionmentioning
confidence: 99%
“…It produces Clostridium perfringens alpha toxin (CPA) along with enterotoxin (CPE) with or without Clostridium perfringens beta 2 toxin (CPB2) [ 31 , 32 ]. It has been reported that C. perfringens is readily detected in foods such as pork, beef, chicken, and sheep [ 33 - 35 ]. In this study, the relative abundance of C. perfringens in chicken feces was the highest among three different livestock species.…”
Section: Discussionmentioning
confidence: 99%
“…Retail meat market is one of the major potential distributors of foodborne illness (Barros et al, 2007; Jeong et al 2017). To date, many researches have focused on the contamination level of retail meat products remaining the market factors of the origin market uninvestigated (Ko et al, 2013; Park et al, 2002; Samadpour et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Market types could also affect the microbiological contamination levels of retail meat (Jeong et al 2017; Ko et al, 2013). The distribution steps vary among market types, and can influence in contamination levels of incoming meat (Park et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…This data is higher than the findings obtained in other countries. For example, in Seoul, Korea, the prevalence of C. perfringens in retail beef was below 16.67% [ 11 ]. While in Lahore city of Pakistan, prevalence of this organism in beef was no more than 1% [ 13 ].…”
mentioning
confidence: 99%